Análisis exploratorio de datos para la planificación de insumos en la Secretaría de Emergencia Nacional del Paraguay (Revista Científica UCOM Scientia, 2025)
The National Emergency Secretariat (SEN) of Paraguay is responsible for managing and reducing disaster risk through participatory policies based on knowledge and technology. However, it faces significant challenges in accurately planning humanitarian supplies due to its reliance on manual processes, which increase the risk of errors and hinder effective budget forecasting and allocation. This article presents an exploratory data analysis of historical humanitarian assistance records from 2018 to 2023, as the initial stage of a broader project aimed at developing an automated needs forecasting system. The study examines three key dimensions—temporal, geographic, and by type of event—to identify operational patterns, seasonal trends, and territorial hotspots. The findings lay the groundwork for evidence-based planning, supporting improved decision-making and more efficient resource allocation in emergency contexts.